2014
DOI: 10.3168/jds.2014-8033
|View full text |Cite
|
Sign up to set email alerts
|

Feeding protein supplements in alfalfa hay-based lactation diets improves nutrient utilization, lactational performance, and feed efficiency of dairy cows

Abstract: Due to the increasing cost of soybean meal and concerns of excess N being excreted into the environment, new protein supplements have been developed. Two products that have shown potential in increasing N utilization efficiency are slow-release urea (SRU; Optigen; Alltech Inc., Nicholasville, KY) and ruminal-escape protein derived from yeast (YMP; DEMP; Alltech Inc.). The objective of this study was to assess the effects of feeding these 2 supplements in alfalfa hay-based [45.7% of forage dietary dry matter (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 49 publications
(74 reference statements)
3
27
0
1
Order By: Relevance
“…Optigen®, a blended, controlled release urea product in a polyester polyurethane coating, allows the diffusion of the urea through micropores that slow down the rate of nitrogen release in the rumen (Galo et al 2003). The dietary concentration of the SRU was chosen based on a previous lactation study (Neal et al 2014). Slowrelease urea has a CP concentration of 256%, which has 11% less N than urea due to the vegetable oil coating of SRU.…”
Section: Cows Experimental Design and Dietsmentioning
confidence: 99%
See 3 more Smart Citations
“…Optigen®, a blended, controlled release urea product in a polyester polyurethane coating, allows the diffusion of the urea through micropores that slow down the rate of nitrogen release in the rumen (Galo et al 2003). The dietary concentration of the SRU was chosen based on a previous lactation study (Neal et al 2014). Slowrelease urea has a CP concentration of 256%, which has 11% less N than urea due to the vegetable oil coating of SRU.…”
Section: Cows Experimental Design and Dietsmentioning
confidence: 99%
“…Milk energy was calculated as (0.0929 × milk fat concentration) + (0.0563 × milk TP concentration) + (0.0395 × milk lactose concentration) (NRC 2001). Estimated NE l value was calculated by total net energy used for maintenance, BW gain, and milk divided by DMI (Neal et al 2014).…”
Section: Energy Partitioning Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to good protein quality, high protein content, complete and reasonable proportion of amino acid composition, providing the right amount of fat, sugar and soluble starch and a variety of minerals and vitamins, alfalfa leaf protein can be employed for feed additives . Many studies have reported that alfalfa leaf protein could replace part of the feed to reinforce feed quality and animal growth. In adult chicken feed, when 50–100% fishmeal was replaced by alfalfa leaf protein, egg production was not affected and egg quality improved; for chick feed, alfalfa leaf protein could replace 50–75% fishmeal, and survival rate was promoted by 3.4–4.2%; in broiler chickens feed, when 7.4–11.8% animal protein feed was replaced by alfalfa leaf protein, average weight increased by 4–11.8% .…”
Section: Alfalfa Leaf Proteinmentioning
confidence: 99%